Synthesis of Substituted Thiazolidinone Derivatives and Study on their Activity - Panwar, Hemant; Chaudhary, Nidhi; Singh, Shishupal; Tyagi, Reena (Asian Journal of Chemistry, 2012)
A series of S-glycosidic linkage bearing thiazolidinones have been prepared. The synthesized derivatives characterized by elemental and spectral analysis (IR, 1H NMR and mass). Furthermore, compounds also evaluated to check their antimicrobial potency against selected panels of microbes. The most potent derivative also screened for its lethal dose.